Paroxythyreus stilleri, a new genus and species of South African Macrocephalini (Hemiptera: Heteroptera: Reduviidae: Phymatinae) with a note on the metathoracic glands and their evaporation areas in the Reduviidae - Jacobs, Dawid H. (Zootaxa, 2025)
Paroxythyreus gen. nov. and its type species P. stilleri sp. nov. (Hemiptera: Heteroptera: Reduviidae: Phymatinae: Macrocephalini) from South Africa are described and illustrated. The metathoracic gland system and evaporative areas in the Reduviidae and Phymatinae are briefly discussed. A unique area of modified cuticle on the metapleuron of P. stilleri is reported and its possible function discussed.